HUBUNGAN KEMAMPUAN MEMBACA KRITIS DENGAN KEMAMPUAN MENULIS KARYA ILMIAH SISWA KELAS XI SMK NEGERI 6 PADANG - May Tiara Anggraini; Rina Sartika; Rahayu Fitri; Ihsan, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to determine students' critical reading skills, how they can write scientific papers, and how critical reading relates to students' ability to write scientific papers in class XI at SMK Negeri 6 Padang. Because these two skills are fundamental to master, this quantitative research uses a correlation approach. The population of this research is students in class XI at SMK Negeri 6 Padang who are registered in 2023/2024. The sample in this research was class XI students, totaling 31 people. The data collection technique uses a questionnaire and the data analysis carried out is correlation analysis between variables. The results of this research are first, the reading habits of the class secondly, the scientific work writing skills of the class third, there is a significant relationship between reading skills and scientific writing skills of class XI students at SMK Negeri 6 Padang. Based on these conclusions, teachers who teach Indonesian language subjects must be more innovative in improving students' reading and writing skills at SMK Negeri 6 Padang